Vascular endothelial growth factor a and proliferation marker in prediction of lymph node metastasis in oral and pharyngeal squamous cell carcinoma - Vipa Boonkitticharoen (2018)
Objective: To explore the effect of Ki-67 and vascular endothelial growth factor A (VEGF-A) expression on the risks of advanced T category (T3,4) and positive lymph node involvement (N+) in oral and pharyngeal squamous cell carcinoma (SCC) compared with laryngeal SCC. Design: Immunohistochemical analysis of prospectively recruited patients. Setting: University-affiliated hospital. Patients: A total of 147 previously untreated patients with different stages of SCC in the oral cavity, pharynx, and larynx. Main Outcome Measures: Relative risks of T3,4 tumor and N+, a risk ratio comparing risks under high vs low marker expression. Results: A significant association of Ki-67 and VEGF-A expression with tumor T category was observed for oral and pharyngeal SCC and for laryngeal SCC (P≤.006). Regarding nodal status, Ki-67 expression was a significant risk factor for N+ in all tumors (P≤.009), whereas VEGF-A expression was related to N+ in oral and pharyngeal SCC only (P<.03). Analytically, Ki-67 expression alone in oral and pharyngeal SCC was associated with a relative risk of N+ of 3.83(95% confidence interval, 1.22-11.99; P=.009),and additional expression of VEGF-A raised the value to 6.12 (2.09-17.93;P<.001). Moreover, the combined expression of both markers was 3.25 times more effective in predicting N+ for T1,2 tumor compared with T3,4 tumor. Conclusions: Proliferative status was a common risk factor for N+ in all of the tumors in this series. Exploitation of VEGF-A in lymph node metastasis in addition to proliferation by oral and pharyngeal SCC but not by laryngeal SCC explains the clinical aggressiveness of oral and pharyngeal SCC, especially the early lymphatic invasion. In the management of cervical lymph nodes, combined expression of Ki-67 and VEGF-A may help identify patients at risk for occult metastases. This study suggests anti-VEGF-A therapy, an additional intervention to the classic antiproliferative regimen, for preventing lymphatic progression of oral and pharyngeal SCC. ©2008 American Medical Association. All rights reserved.